Thrombomodulin Gene Polymorphism (C1418T) is Associated with the Development of Coronary Allograft Vasculopathy. (September 2013) - Tsai, C.S.; Lin, Y.W.; Shih, C.C.; Chen, Y.H.; Lin, C.Y.; Tsai, Y.T.; Lee, C.Y.; Shih, C.M.; Huang, C.Y.; Chung, H.H.; Lin, F.Y.
Thrombomodulin (TM) is the endothelial cell membrane-bound anticoagulant protein cofactor in the thrombin-mediated activation of protein C. Previous evidence has been reported regarding the association between TM polymorphisms and coronary artery disease. Allograft rejection-mediated vasculopathy is the main cause of death at more than one year after heart transplantation. However, whether TM polymorphism is associated with allograft rejection is still unclear. We analyzed the TM gene polymorphism C1418T using allele-specific primers in a PCR assay in 60 patients who underwent heart transplantation. The retrospective clinical data were collected and tested for any correlations with the TM gene polymorphism. We separated the patients into 2 groups according to their TM genotype (group 1: CC genotype; group 2: CT or TT genotype). Additionally, we generated expression constructs (TM full length-C1418 and TM full length-T1418) and performed in vitro studies to explore the correlation between the TM C1418T polymorphism and the migration of smooth muscle progenitor cells and monocytes, which may be involved in the development of vasculopathy. The results showed that the levels of CD68, C4d, PAS, and Masson staining in the CT/TT genotype group increased at year 1 and continued to increase throughout the 3 years. These levels were higher than those observed in the CC genotype group. The ISHLT-WF2004 grade of the CT/TT genotype group was significantly different from that of the CC genotype group at the same time point post-transplantation. The coronary allograft vasculopathy (CAV) score was significantly different between the CC and CT/TT genotype groups at 1 and 3 years post-transplantation. Our in vitro studies demonstrate that both smooth muscle progenitor cells and monocytic THP-1 cells with either the CT-1418 or the TT-1418 TM genotype have higher migratory abilities than cells with the CC-1418 genotype. Our results support a significant association between the TM C1418T polymorphism and the development of CAV after heart transplantation in the short- to medium-term.